Madness Triumphant : a Reading of Lucan's Pharsalia. - Fratantuono, Lee (Lexington Books, 2012)
Madness Triumphant: A Reading of Lucan's Pharsalia offers the most detailed and comprehensive analysis of Lucan's epic poem of the civil war between Caesar and Pompey to have appeared in English. In the manner of his previous books on Virgil and Ovid, Professor Fratantuono considers the Pharsalia as an epic investigation of the nature of fury and madness in Rome, this time during the increasing insanity of Nero's reign.